The Legislative Framework of Career Guidance and Counselling in Serbia - Miljković, Jovan; Čairović Pavlović, Neda; Robertson, Kristina (Studies in Teaching and Education, 2024)
Over the past few decades, the concept of a career has undergone significant transformation. It has become less linear and more heterogeneous and multifaceted, often marked by frequent changes and numerous parallel and lateral paths. Within this context, career guidance and counselling have emerged as leading concepts in various sectoral polities, both in the European Union and in Serbia, and are undoubtedly at the forefront of educational polities. To effectively manage career guidance and counselling (CGC) and optimize the expected outcomes from this phenomenon and activity, a consistent and carefully designed legislative framework is necessary. Using a qualitative research approach, we conducted a study to understand how the phenomenon of career guidance and counselling is perceived in the legislative documents of the Republic of Serbia. We operationalised the main research question by examining seven elements of CGC: understanding the concept, objectives, programmes, activity holders, career practitioners, target groups, and outcomes. Our methods included descriptive and comparative analysis, as well as a review of 19 documents from the sectors of youth, education (from primary to adult education), and employment. This was done with the aim of covering all ages and life roles in which CGC may play a role. The research results indicate that CGC, as a cross-sectoral activity, is unevenly articulated across different polity sectors. There is a predominant orientation towards youth, the educational sector, and the service of informing about career, out of the three areas of CGC services. The study highlights the need for the adoption of an integrative document and the establishment of a coordinating body for this activity, as well as the mandatory application of existing CGC standards.